Subversive images of women in medieval English literature: a selective reading - F. Shams, Sheikh (BRAC University, 2010)
It is commonly assumed that medieval society is hostile to women’s power. Women are continuously contained and constrained by the patriarchal norms of medieval Europe to strengthen the heroic ideals of masculinity, while maintaining the ideals of the domestic private sphere. This study shows that even within the domestic private sphere, women exert considerable amount of power to influence men’s actions. In fact, what we see are models of powerful women capable of damaging the heroic ideals of men. Hence there is a tendency to control women’s power. This essay explores how far this tendency to control is actually successful. If not then we are witnessing a tension between dominant patriarchal ideology and the subversive images of women. The resistance that women characters in medieval literature's pose to the hegemonic ideology is a matter of particular interest of this paper. At the same time, the nature of their containment and appropriation is also something that this paper wishes to examine.